IMPLEMENTASI REACT SERVER COMPONENT DAN SERVER ACTION UNTUK MENINGKATKAN PERFORMA APLIKASI WEB - Mulyanto, Yudi; Haryanti, Eka; Lazarus, Lazarus (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2024)
This research explores the use of React Server Components (RSC) and Server Action to improve web application performance, with a focus on the legislative election vote counting system in Sumbawa Regency, West Nusa Tenggara for internal party needs. Looking at the geographical and infrastructural challenges in Sumbawa, this research aims to overcome the limitations of signal and telecommunication infrastructure distribution through the use of RSC and Server Action. RSC allows the server to render components while maintaining interactivity on the client side, reducing load and speeding up load times. Advantages include avoiding chained network requests and minimizing Javascript on the client side, which is especially beneficial in areas with limited internet connectivity. Server Action eliminates the traditional API layer, reducing latency and improving application responsiveness. By utilizing Next.js as a framework, this research aims to maximize the use of server resources and minimize client resource requirements, improving speed in vote counting and reporting. This implementation is expected to not only improve overall application performance but also ensure smooth application accessibility in areas with limited internet infrastructure.